Urticaria caused by cold in an adolescent - Adianez Sugrañes Montalván; Eduardo Barreto Suarez; Lidyce Quesada leyva (Centro Provincial de Información de Ciencias Médicas, 2019)
The case report of a 17 years peasant white patient, is presented with a history of allergic rhinitis for approximately 4 years, who visited the Alergology Service of Eduardo Agramonte Piña Provincial Hospital in Camagüey, to present a sustained urticariform pattern exacerbated with time in spite of the diet and general measures.  An specific provocation test which was positive was carried out; therefore, an inducible chronic urticaria of physical type was diagnosed, caused specifically by cold. Treatment with ketotifen was indicated and 6 months later the test was repeated, showing a favorable result.